2017
DOI: 10.3233/rnn-160691
|View full text |Cite
|
Sign up to set email alerts
|

Whole body vibration (WBV) following spinal cord injury (SCI) in rats: Timing of intervention

Abstract: WBV started 14 days after SCI provides the most benefit (RHI, bladder); starting at 1day after SCI provides no benefit and starting at 28 days may be detrimental. Increasing the intensity of WBV to twice daily did not provide additional benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Two studies [78,79] showed motor performance improvement and attention. In addition, WBV enhanced muscle strength, isometric force production in semitendinosus skeletal muscle and decreased the fatiguing effects of intensive synaptic muscle stimulation [38,80]. Furthermore, WBV improved motor coordination from 14-to 28-days post-ischemia and muscle strength of the upper limbs at 21-and 28-days post-ischemia [61], which corroborates the notion that WBV is known to improve neuromuscular performance [40].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Two studies [78,79] showed motor performance improvement and attention. In addition, WBV enhanced muscle strength, isometric force production in semitendinosus skeletal muscle and decreased the fatiguing effects of intensive synaptic muscle stimulation [38,80]. Furthermore, WBV improved motor coordination from 14-to 28-days post-ischemia and muscle strength of the upper limbs at 21-and 28-days post-ischemia [61], which corroborates the notion that WBV is known to improve neuromuscular performance [40].…”
Section: Discussionsupporting
confidence: 72%
“…In contrast, some studies [89,91,92] designed for evaluate injury effects of WBV, decided in only 1 bout by a long-time exposure (varying from 90 min to 240 min). Furthermore, some studies modeling SCI applied two frequencies and one amplitude, which are within the normal range of motoneuron discharges and are well tolerated by the rats [38,[73][74][75]. Different devices to generate mechanical vibration were used, such as an alternating model [38,62,[72][73][74], a vertical model [62,69,93] and those which used a custom type of platform adapted to generate vibration stimuli in animals models [59,68,[77][78][79][86][87][88], which indicates a heterogeneity as for the vibration stimuli model on the selected studies, and can increase its translational value for different clinical approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these considerations, in our previous work we evaluated the effects of three WBV training protocols, differing in vibration frequency and vibration exposure time, on synaptic plasticity in an experimental mouse model, by means of in vitro extracellular recordings in hippocampal slices from 4to 24-month-old mice (Cariati et al, 2021). It was previously suggested that synaptic plasticity is positively affected by WBV training, both in rodents (Manthou et al, 2017) and in humans (Fuermaier et al, 2014;Regterschot et al, 2014), probably through the involvement of sensory stimulation leading to cognitive enhancement. In agreement with these studies, our results showed that WBV training can modulate synaptic plasticity differently, depending on the protocol used, and that the best effects are related to the training protocol characterized by a low vibration frequency and a longer recovery time.…”
Section: Introductionmentioning
confidence: 99%